Chile enters the League of Nations in an inter-war world (Revista de Estudios Europeos, 2024)
Following the conclusion of the Great War, a new scenario began to unfold under the framework of a multilateral organization, such as the League of Nations, in which Chile would not remain indifferent. Consequently, this article addresses the most significant milestones that occurred within the National Congress to secure its approval for the government. Additionally, through the analysis of press coverage from the period, the article will present the most relevant moments and themes that were communicated to the Chilean public regarding the implications of joining the League of Nations.
Keywords: Chile; League of Nations; National Congress; Press; Foreign Policy